Novel role of cardiovascular MRI to contextualise tuberculous pericardial inflammation and oedema as predictors of constrictive pericarditis - Giliomee, L. J.; Doubell, A. F.; Robbertse, P. S.; John, T. J.; Herbst, P. G. (Frontiers in Cardiovascular Medicine, 2024)
Tuberculosis (TB) and human immunodeficiency virus/acquired immunodeficiency syndrome have reached epidemic proportions, particularly affecting vulnerable populations in low- and middle-income countries of sub-Saharan Africa. TB pericarditis is the commonest cardiac manifestation of TB and is the leading cause of constrictive pericarditis, a reversible (by surgical pericardiectomy) cause of diastolic heart failure in endemic areas. Unpacking the complex mechanisms underpinning constrictive haemodynamics in TB pericarditis has proven challenging, leaving various basic and clinical research questions unanswered. Subsequently, risk stratification strategies for constrictive outcomes have remained unsatisfactory. Unique pericardial tissue characteristics, as identified on cardiovascular magnetic resonance imaging, enable us to stage and quantify pericardial inflammation and may assist in identifying patients at higher risk of tissue remodelling and pericardial constriction, as well as predict the degree of disease reversibility, tailor medical therapy, and determine the ideal timing for surgical pericardiectomy.